Building Barriers, but for whom - Cole, Sebastian; Winberg, Philip (My University, 2018)
The impacts of the terrorist attacks on 11th of September 2001 in New York had a profound effect and the aftermath embraced universal consequences and repercussions. It was perceived by the International Maritime Organization and the European Union that similar attacks could be imminent and both bodies rapidly adopted new maritime and port security regulations to avert further events occurring. On a local level, the Member States of the two bodies had to develop their own national regulations. In this context, the thesis focuses on the barriers that Swedish port organisations have identified in order to comply with the regulatory security framework on a global, international and national level. Using a deductive approach, this explanatory case study is based on a wide electronic survey targeted at public port organisations in Sweden. The survey was based on the theoretical framework constructed. Furthermore, in-depth interviews were conducted with a wide range of special advisers and experts in the field of study. From this research, two main findings emerged; while the current regulatory security framework is sound, this still requires that all parties are actively involved. For all parties to be actively involved, the knowledge-creation and information-sharing must be improved on both an inter- and intra-organisational level.
Keywords: Informations- och kommunikationsteknik; Innovation och entreprenörskap (nyttiggörande); Systemvetenskap, informationssystem och informatik; Marin teknik; Information & Communication Technology; Innovation & Entrepreneurship; Information Systems; Marine Engineering